Multicentric Italian survey on daily practice for autoimmune pancreatitis: Clinical data, diagnosis, treatment, and evolution toward pancreatic insufficiency. Issue 6 (July 2020) - Barresi, Luca; Tacelli, Matteo; Crinò, Stefano Francesco; Attili, Fabia; Petrone, Maria Chiara; De Nucci, Germana; Carrara, Silvia; Manfredi, Guido; Capurso, Gabriele; De Angelis, Claudio Giovanni; Crocellà, Lucia; Fantin, Alberto; et al.
Background: Autoimmune pancreatitis (AIP) is a rare, and relatively new, form of chronic pancreatitis. The management of AIP can vary considerably among different centres in daily clinical practice. Objectives: The aim of this study is to present a picture of epidemiological, clinical characteristics, outcomes, and the real-life practice in terms of management in several academic and non-academic centres in Italy. Methods: Data on the clinical presentation, diagnostic work-up, treatments, frequency of relapses, and long-term outcomes were retrospectively collected in a cohort of AIP patients diagnosed at 14 centres in Italy. Results: One hundred and six patients were classified as type 1 AIP, 48 as type 2 AIP, and 19 as not otherwise specified. Epidemiological, clinical, radiological, and serological characteristics, and relapses were similar to those previously reported for different types of AIP. Endoscopic cytohistology was available in 46.2% of cases, and diagnostic for AIP in only 35.2%. Steroid trial to aid diagnosis was administered in 43.3% cases, and effective in 93.3%. Steroid therapy was used in 70.5% of cases, and effective in 92.6% of patients. Maintenance therapy with low dose of steroid (MST) was prescribed in 25.4% of cases at a mean dose of 5 (±1.4) mg/die, and median time of MST was 60 days. Immunosuppressive drugs were rarely used (10.9%), and rituximab in 1.7%. Faecal elastase-1 was evaluated in only 31.2% of patients, and was pathological in 59.2%. Conclusions: In this cohort of AIP patients, diagnosis and classification for subtype was frequently possible, confirming the different characteristics of AIP1 and AIP2 previously reported. Nevertheless, we observed a low use of histology and steroid trial for a diagnosis of AIP. Steroid treatment was the most used therapy in our cohort. Immunosuppressants and rituximab were rarely used. The evaluation of exocrine pancreatic insufficiency is underemployed considering its high prevalence.